A case for risk leased deposit insurance system in India - Ajit, D. (1998)
The deposit and credit insurance system in India is examined in the light of experiences of other countries - both developed and developing. The study examines important issues such as flat fee, risk-based insurance system for banks/non-banks, ownership of deposit insurance agency, continuation of credit guarantee scheme, etc. As regards deposit insurance scheme for NBFCs the study cautions its introduction at this stage as it could amplify the regulatory divergence and moral hazard problems. It makes the case for introduction of a risk based deposit insurance scheme for NBFCs only after putting in place an effective regulatory and supervisory system for them. - Reproduced
Keywords: Insurance - India; Insurance